1997
DOI: 10.1111/j.1399-3038.1997.tb00150.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Epstein Barr virus antibodies, serum IgE and atopic disease

Abstract: It is currently accepted that viral infections may influence the development of atopy. In the present study we evaluated serum IgE levels as well as the prevalence of symptoms indicative of atopic disease and EBV antibodies in 353 children aged from 1 month to 19 years. Antibodies against EBV were detected by immunofluorescence. IgE levels in serum were measured by enzyme immunoassay. Dividing the study population according to EBV seropositivity and age, we noted that the prevalence of high IgE levels (> 2 s.d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
24
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 39 publications
3
24
0
Order By: Relevance
“…The protective effects may be related to exposure to manure and microbial exposure in the home [68,69]. Several different pathogens have been suggested to have a protective role against AD and atopy in general, including bacterial endotoxins, helminthes, herpesviridae, farm animals, dogs, unpasteurized milk, and the abundant infectious exposures of early day care [70][71][72][73][74]. Silverberg et al found that a single episode of wild-type varicellazoster virus (chickenpox) infection in the first 8-10 years of life was inversely associated with subsequently developing AD [73], as well as long-term decreased serum IgE levels, peripheral blood lymphocyte, monocyte, and basophil counts [75].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…The protective effects may be related to exposure to manure and microbial exposure in the home [68,69]. Several different pathogens have been suggested to have a protective role against AD and atopy in general, including bacterial endotoxins, helminthes, herpesviridae, farm animals, dogs, unpasteurized milk, and the abundant infectious exposures of early day care [70][71][72][73][74]. Silverberg et al found that a single episode of wild-type varicellazoster virus (chickenpox) infection in the first 8-10 years of life was inversely associated with subsequently developing AD [73], as well as long-term decreased serum IgE levels, peripheral blood lymphocyte, monocyte, and basophil counts [75].…”
Section: Hygiene Hypothesismentioning
confidence: 99%
“…24 Moreover, both runny nose and herpes-type viral infections, including varicella, herpes (zoster, febrilis, labialis), exanthema subitum, and stomatitis, are associated with decreased risk of asthma at school age. 27 This is in contrast to the proallergy and asthma effects seen with other respiratory viral infections such as respiratory syncytial virus (RSV), which can induce a virus-specific IgE response.…”
Section: Disussionmentioning
confidence: 99%
“…Moreover, previous studies demonstrated decreased atopic disease after WTVZV infection. [24][25][26][27]40 AD and the aforementioned atopic disorders constitute major public health and economic burdens. Previous studies using cost-effectiveness models have suggested that widespread varicella vaccination programs in childhood are cost-effective compared with the financial burden of WTVZV infection and its complications.…”
Section: Disussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4,7 Infections with EBVand cytomegalovirus have previously been implicated in influencing allergic disorders, but their precise role remains controversial. Some studies have suggested allergyprotective 8,9 or allergy-promoting 10-12 effects, whereas others could not demonstrate a clear role for EBV or cytomegalovirus in the pathogenesis of allergic disorders. 13,14 A previous study from our group showed an inverse relation between EBV infection and IgE sensitization in a cohort of Swedish 2-year-old infants.…”
mentioning
confidence: 95%